Effects of interval and continuous exercise training on autonomic cardiac function in COPD patients. (13th August 2014) - Rodríguez, Diego A.; Arbillaga, Ane; Barberan‐Garcia, Anael; Ramirez‐Sarmiento, Alba; Torralba, Yolanda; Vilaró, Jordi; Gimeno‐Santos, Elena; Gea, Joaquim; Orozco‐Levi, Mauricio; Roca, Josep; Marco, Ester
Abstract: Background and Aim: Both interval (IT) and continuous (CT) exercise training results in an improvement of aerobic capacity in patients with chronic obstructive pulmonary disease (COPD); however, their effects on cardiac autonomic function remains unclear. The aim of our study was to evaluate the effect of a supervised CT vs IT on autonomic cardiac function in COPD patients. Methods: COPD patients were divided into two different groups according to training modality (IT or CT). Autonomic cardiac dysfunction (ACD) was defined as a heart rate recovery lower than 12 bpm heart rate after the first minute of maximal exercise (HRR1 ) and an abnormal chronotropic response (CR) to exercise (<80%). Results: A total of 29 patients {mean [standard deviation (SD)] age: 68 (8) years, %FEV1 : 42 (13) predicted} were trained (15 subjects in the CT group, 14 subjects in the IT group). After training, both groups increased peak oxygen consumption [mean difference ΔVO2 peak: 156 mL/min ( P  = 0.04) on IT; and 210 mL/min ( P  = 0.01) on CT], HRR1 [IT, from 10.4 (5) to 13.8 (5) bpm ( P  = 0.04); and CT, from 14.3 (5) to 17.7 (5) bpm ( P  = 0.04)] and CR [IT, from 57% (22) to 81% (9) ( P  = 0.001); and CT, from 48% (28) to 73% (17) ( P  = 0.001)]. Sixteen patients showed ACD. Among these patients, HRR1 ( P  = 0.01 for IT and P  = 0.04 for CT) and CR ( P  = 0.001 for IT and P  = 0.002 for CT) were enhanced after training. Conclusions: Both IT and CT exercise training improve heart rate recovery and CR in COPD patients. These benefits could help to individualize exercise training.